2006
DOI: 10.1073/pnas.0510606103
|View full text |Cite
|
Sign up to set email alerts
|

Effective expansion of alloantigen-specific Foxp3+CD25+CD4+regulatory T cells by dendritic cells during the mixed leukocyte reaction

Abstract: Thymic-derived CD25Recent reports have shown that Tregs proliferate and retain their antigen-dependent suppressive functions when the APCs are antigen-loaded mature dendritic cells (DCs) (16-18). When Tregs specific for a pancreatic islet ␤ cell antigen are stimulated by DCs together with IL-2, the expanded antigen-specific T cells regulate the development of autoimmune diabetes in nonobese diabetic mice and do so much more effectively than polyclonal populations (18). From the perspective of suppressing unwan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
153
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(172 citation statements)
references
References 33 publications
(51 reference statements)
14
153
2
1
Order By: Relevance
“…Recent studies have identified different subsets of DCs that have different abilities to activate Th and Tregs and can induce either immunity or tolerance (47)(48)(49)(50)(51). By targeting the MUC1 Ag to the appropriate population of DCs, one might be able to dictate the nature and outcome of the DC-T cell interaction to favor the induction of Th cells over Tregs, thereby promoting the establishment of effective tumor-specific memory CTLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified different subsets of DCs that have different abilities to activate Th and Tregs and can induce either immunity or tolerance (47)(48)(49)(50)(51). By targeting the MUC1 Ag to the appropriate population of DCs, one might be able to dictate the nature and outcome of the DC-T cell interaction to favor the induction of Th cells over Tregs, thereby promoting the establishment of effective tumor-specific memory CTLs.…”
Section: Discussionmentioning
confidence: 99%
“…D, Specific lysis of the MUC1 ϩ tumor RMA-MUC1. Pooled LN cells were incubated for 4 h with 51 Cr-labeled RMA or RMA-MUC1 targets in triplicate.…”
Section: Dc-muc1 Vaccine Elicits Muc1-specific Tregs That Limit the Fmentioning
confidence: 99%
“…DC can differentiate T regs in the thymus [78] and in the periphery [79], and expand them once the T regs have formed [80][81][82]. Antigen-specific T regs are much more effective than polyclonal populations in suppressing immunity in vivo [79,[81][82][83]. For many years, the major approach to the induction of peripheral tolerance has been to inject very large doses of antigen.…”
Section: Tolerogenicity Another Side Of Immunogenicitymentioning
confidence: 99%
“…Therefore, polyspecific CD4 + CD25 high cells are currently being evaluated after stem cell transplantation [13]. However, under nonlymphopenic conditions as seen in patients with autoimmune diseases or in patients after organ transplantation, polyspecific Treg cells have so far been largely ineffective in controlling immune responses [5,14,15] [24], and CD137 (4-1BB) [25] were described as Treg-cell activation markers after polyspecific Treg-cell activation.In this manuscript, we demonstrated for the first time that LAP and GARP can be used for the isolation of highly pure alloantigenspecific Treg cells. In addition, we showed that CD40 ligand (CD154) is not expressed on naïve and activated Treg cells.…”
mentioning
confidence: 99%